Presenting Characteristics Associated With Outcome in Children With Severe Traumatic Brain Injury: A Secondary Analysis From a Randomized, Controlled Trial of Therapeutic Hypothermia*. Issue 10 (October 2018) - Rosario, Bedda L.; Horvat, Christopher M.; Wisniewski, Stephen R.; Bell, Michael J.; Panigrahy, Ashok; Zuccoli, Giulio; Narayanan, Srikala; Balasubramani, Goundappa K.; Beers, Sue R.; Adelson, P. David
Abstract : Objectives: To identify injury patterns and characteristics associated with severe traumatic brain injury course and outcome, within a well-characterized cohort, which may help guide new research and treatment initiatives. Design: A secondary analysis of a phase 3, randomized, controlled trial that compared therapeutic hypothermia versus normothermia following severe traumatic brain injury in children. Setting: Fifteen sites in the United States, Australia, and New Zealand. Patients: Children (< 18 yr old) with severe traumatic brain injury. Measurements and Main Results: Baseline, clinical, and CT characteristics of patients ( n = 77) were examined for association with mortality and outcome, as measured by the Glasgow Outcome Scale—Extended Pediatric Revision 3 months after traumatic brain injury. Data are presented as odds ratios with 95% CIs. No demographic, clinical, or CT characteristic was associated with mortality in bivariate analysis. Characteristics associated with worse Glasgow Outcome Scale—Extended Pediatric Revision in bivariate analysis were two fixed pupils (14.17 [3.38–59.37]), abdominal Abbreviated Injury Severity score (2.03 [1.19–3.49]), and subarachnoid hemorrhage (3.36 [1.30–8.70]). Forward stepwise regression demonstrated that Abbreviated Injury Severity spine (3.48 [1.14–10.58]) and midline shift on CT (8.35 [1.05–66.59]) were significantly associated with mortality. Number of fixed pupils (one fixed pupil 3.47 [0.79–15.30]; two fixed pupils 13.61 [2.89–64.07]), hypoxia (5.22 [1.02–26.67]), and subarachnoid hemorrhage (3.01 [1.01–9.01]) were independently associated with worse Glasgow Outcome Scale—Extended Pediatric Revision following forward stepwise regression. Conclusions: Severe traumatic brain injury is a clinically heterogeneous disease that can be accompanied by a range of neurologic impairment and a variety of injury patterns at presentation. This secondary analysis of prospectively collected data identifies several characteristics associated with outcome among children with severe traumatic brain injury. Future, larger trials are needed to better characterize phenotypes within this population. Abstract : Supplemental Digital Content is available in the text.